The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12875-021-01422-y
|View full text |Cite
|
Sign up to set email alerts
|

Individual-level socioeconomic status and contact or familiarity with people with mental illness: a cross-sectional study in Wuhou District, Chengdu, Southwest China

Abstract: Background People with mental illness (PWMI) often suffer from public stigma, which can make them unwilling to seek help and reduce access to early treatment. The aims of this study were to determine attitudes towards PWMI among the general public in a Chinese sample and to explore the relationships with sociodemographic characteristics. Methods A community-based, cross-sectional study was conducted from March to June 2019. The participants’ attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Those in the worst financial position were 1.52 (1.37, 1.68) times more likely to report difficulty talking to a person with mental illness than those in the most secure financial position. More recent research from both the UK and China finds a similar association between lower socioeconomic status and a greater desire for social distance from people experiencing mental health problems (34,35).…”
Section: Discussionmentioning
confidence: 87%
“…Those in the worst financial position were 1.52 (1.37, 1.68) times more likely to report difficulty talking to a person with mental illness than those in the most secure financial position. More recent research from both the UK and China finds a similar association between lower socioeconomic status and a greater desire for social distance from people experiencing mental health problems (34,35).…”
Section: Discussionmentioning
confidence: 87%
“…Generally, people with more years of age, female gender, and higher income show a more favorable attitude towards people with mental disorders. 19 , 20 , 35 , 36 It is necessary to consider especially low- and middle-income countries, such as Colombia, because poverty and inequity are a syndemic favoring SDRMD. In these countries, there is a high frequency of people with little formal education, people with mental health illiteracy, and people living with mental disorders without access to health services, to the point that low- and middle-income countries account for 80% of the mental health disease burden worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…SES has been shown to be associated with mental illness stigma (Wang et al, 2021 ; Foster and O’Mealey, 2022 ). The results of the study suggested that participants with middle SES tend to have more stigma as evident in other Asian countries such as Pakistan, India, and China (Knifton, 2012 ).…”
Section: Discussionmentioning
confidence: 99%